2003
DOI: 10.1109/tns.2003.821602
|View full text |Cite
|
Sign up to set email alerts
|

Carrington flare of 1859 as a prototypical worst-case solar energetic particle event

Abstract: Recent analyses of ice core samples indicate that the Carrington flare of 1859 was the largest event observed in the past 500 years. These ice core data yield estimates of the proton fluence for energies greater than 30 MeV, but provide no other spectrum information. Assuming that the proton energy distribution for such an event is similar to that measured for other recent, large events, total ionizing doses in deep space are estimated for these hypothetical worst-case spectra. These estimated doses, as large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…The latter curve was then multiplied by two to produce a further spectrum, referred to as SEPEM Extreme SEP (x2),. These simulated spectra are compared in the figure with three spectra recorded in space -on October 2003, August 1972 and July 2012 (aboard STEREO A) -as well as with an estimate of the spectrum of the 1 September, 1859 Carrington event published earlier in [49].…”
Section: Statistical Models Of Sep Radiationmentioning
confidence: 99%
“…The latter curve was then multiplied by two to produce a further spectrum, referred to as SEPEM Extreme SEP (x2),. These simulated spectra are compared in the figure with three spectra recorded in space -on October 2003, August 1972 and July 2012 (aboard STEREO A) -as well as with an estimate of the spectrum of the 1 September, 1859 Carrington event published earlier in [49].…”
Section: Statistical Models Of Sep Radiationmentioning
confidence: 99%
“…Analyses of possible doses from a solar energetic particle event similar to the Carrington Event of 1859 have been carried out for purposes of estimating doses in deep space for electronics (Townsend et al, 2003) and humans (Stephens et al, 2005); and for humans in low-Earth orbit (Townsend et al, 2004). In these analyses various spectral shapes were assumed.…”
Section: Previous Analyses Of Organ Dosesmentioning
confidence: 99%
“…Such doses might result in component failure, especially for many commercial off the shelf (COTS) parts, which have not been radiation-hardened. In Townsend et al (2003), doses in silicon materials shielded by aluminum shield thicknesses comparable to those found in manned and unmanned spacecraft were calculated for deep space. The values obtained indicated that a Carrington-type event could present a significant hazard to onboard electronics.…”
Section: Previous Analyses Of Electronic Doses In Deep Spacementioning
confidence: 99%
See 2 more Smart Citations